Liposomes and nanotechnology in drug development: focus on oncotargets - Kozako T (Dove Medical Press, 2012)
Tomohiro Kozako,1 Naomichi Arima,2 Makoto Yoshimitsu,3 Shin-Ichro Honda,1 Shinji Soeda11Department of Biochemistry, Faculty of Pharmaceutical Sciences, Fukuoka University, Fukuoka, Japan; 2Division of Hematology and Immunology, Center for Chronic Viral Diseases, Graduate School of Medical and Dental Sciences, Kagoshima University, Kagoshima, Japan; 3Department of Hematology and Immunology, Kagoshima University Hospital, Kagoshima, JapanAbstract: Nanotechnology is the development of an engineered device at the atomic, molecular, and macromolecular level in the nanometer range. Advances in nanotechnology have proven beneficial in therapeutic fields such as drug-delivery and gene/protein delivery. Antigen delivery systems are important for inducing and modifying immune responses. In cellular immunity, cytotoxic T lymphocytes (CTLs) are important in the host defense against tumors. Key to the development of CTL-inducible vaccines is the ability to deliver antigens to antigen-presenting cells efficiently and to induce the subsequent activation of T cell-mediated immunity without adjuvants, as they can induce excessive inflammation leading to systemic febrile disease. Since expression and cloning methods for tumor-associated antigens have been reported, cancer vaccines that induce effective cell immunity may be promising therapeutic candidates, but Th2 cells are undesirable for use in cancer immunotherapy. Peptide vaccines have immunological and economic advantages as cancer vaccines because CTL epitope peptides from tumor-associated antigens have high antigen-specificity. However, cancer vaccines have had limited effectiveness in clinical responses due to the ability of cancer cells to “escape” from cancer immunity and a low efficiency of antigen-specific CTL induction due to immunogenic-free synthetic peptides. In contrast, carbohydrate-decorated particles such as carbohydrate-coated liposomes with encapsulated antigens might be more suitable as antigen delivery vehicles to antigen-presenting cells. Oligomannose-coated liposomes (OML) can eliminate established tumors in mouse cancer models. In addition, OMLs with an encased antigen can induce antigen-specific CTLs from peripheral blood mononuclear cells obtained from patients. Feasibility studies of OML-based vaccines have revealed their potential for clinical use as vaccines for diseases where CTLs act as effector cells. Furthermore, use of the hepatitis B core particle, in which tumor-antigen epitopes are set, has consistently been shown to induce strong CTL responses without the use of an adjuvant. Thus, nanoparticles may provide a new prophylactic strategy for infectious disease and therapeutic approaches for cancer via the induction of T-cell immunity.Keywords: adult T cell leukemia, cytotoxic T lymphocytes, oligomannose-coated liposomes, vaccine